AB0682 EXPRESSION AND SIGNIFICANCE ANALYSIS OF PEROXIREDOXIN 6 IN RHEUMATOID ARTHRITIS PATIENTS - Guo, H.; Zheng, X.; Wang, R.; Zheng, Y.; Zhang, W.; Zhong, X.; Long, L. (Annals of the rheumatic diseases, 2024)
Background:Rheumatoid arthritis(RA) is a systemic autoimmune disease,which causes joint inflammation, cartilage degeneration and bone erosion. Although the pathophysiological of RA mechanism is not yet fully documented,previous studies have shown that oxidative stress is an important part of the pathogenesis of RA. Peroxiredoxin 6(Prdx6), a newly discovered member of the peroxidase family, has both glutathione-peroxidase activity and phospholipase A2 activity, and plays an important role in anti-oxidative stress damage and apoptosis regulation. Current researchs on Prdx6 to attenuate oxidative damage has focused on the respiratory, nervous, and digestive systems, with fewer studies on rheumatic and immune systems.Objectives:The purpose of this study was to investigate the expression of Prdx6 in serum of patients with RA and its correlation with disease activity,inflammatory indicators.Methods:57 patients diagnosed with RA and 31 demographically matched healthy control subjects participated in this study.Clinical datas of enrolled RA patients were collected,including disease activity, inflammatory markers, cytokines, and immune markers. Disease activity indices of patients were calculated with Disease Activity Score-28 Index(DAS-28). The levels of Prdx6 in serum samples were measured by Enzyme-Linked Immunosorbent Assay(ELISA). RA patients were categorized into two groups according to disease activity: low-moderate disease activity and high disease activity. The results obtained were analyzed by multivariate statistical analysis.Results:The serum Prdx6 level of RA patients was significantly decreased compared with that of healthy control group(1.307±0.500ng/ml vs 2.051±0.775ng/ml, p<0.05). Additionally,erythrocyte sedimentation rate(ESR) was faster in the group with high disease activity than the group with low-moderate disease activity(p<0.05). However,there were no statistically significant differences in immunoglobulin,complement,rheumatoid factor(RF),C-reactive proteinand(CRP),anti-cyclic citrullinated peptide(CCP) antibodies between patients with different levels of disease activity. Meanwhile,disease activity and ESR were negatively correlated with prdx6 level(rs -0.284,p<0.05;rs -0.332,p<0.05). But there was no correlation between prdx6 levels and CRP, IL-6, TNF-ɑ, immunoglobulin, RF,anti-CCP antibodies.Conclusion:Our study shows that prdx6 expression is decreased in RA patients and it was negatively correlated with disease activity and ESR,but its specific pathway of action is unclear and needs further study. Exogenous supplement of Prdx6 may alleviate the oxidative stress damage in RA patients and may be one of the treatment methods for RA.REFERENCES:[1] Wu H, Wu R, Liu T, et al. Peroxiredoxin 6 alleviates high glucose-induced inflammation and apoptosis in HK-2 cells by inhibiting TLR4/NF-κB signaling[J]. Ann Transl Med. 2023;11(2):41.[2] Chen X, Tzekov R, Su M, et al. Hydrogen peroxide-induced oxidative damage and protective role of peroxiredoxin 6 protein via EGFR/ERK signaling pathway in RPE cells[J]. Front Aging Neurosci. 2023;15:1169211.[3] Quiñonez-Flores CM, González-Chávez SA, Del Río Nájera D,et al. Oxidative Stress Relevance in the Pathogenesis of the Rheumatoid Arthritis: A Systematic Review. Biomed Res Int. 2016;2016:6097417.[4] Zamudio-Cuevas Y, Martínez-Flores K, Martínez-Nava GA,et al. Rheumatoid Arthritis and Oxidative Stress[J]. Cell Mol Biol (Noisy-le-grand). 2022;68(6):174-184.Acknowledgements:NIL.Disclosure of Interests:None declared.